A Dynamical Paradigm for Molecular Cell Biology. Issue 7 (July 2020) - Tyson, John J.; Novak, Bela
Abstract : The driving passion of molecular cell biologists is to understand the molecular mechanisms that control important aspects of cell physiology, but this ambition is often limited by the wealth of molecular details currently known about these mechanisms. Their complexity overwhelms our intuitive notions of how molecular regulatory networks might respond under normal and stressful conditions. To make progress we need a new paradigm for connecting molecular biology to cell physiology. We suggest an approach that uses precise mathematical methods to associate the qualitative features of dynamical systems, as conveyed by 'bifurcation diagrams', with 'signal–response' curves measured by cell biologists. Highlights: A dynamical system of interacting genes, proteins, and metabolites underlies the physiological properties of every living cell. To understand the behavior of these molecular mechanisms requires a disciplined mathematical theory of biochemical reaction networks. The proper approach to this problem is based on the 'qualitative theory' of nonlinear differential equations. The link between theory and experiment is the identification of the mathematician's 'one-parameter bifurcation diagram' with the physiologist's signal–response curve.